Developing Local Culture-Based Instructional Materials of English Reading for Social Welfare Learners - Helen Moneka; Yukamana, Hanni; Mayasari, Santi (Journal of Language and Literature Studies, 2025)
The development of instructional materials plays a crucial role in improving students’ learning outcomes, particularly in the context of English reading comprehension at the tertiary education level. At the Social Welfare Department of Institut Teknologi Pagar Alam (ITPA), there is a distinct lack of instructional resources that are not only pedagogically sound but also culturally relevant and aligned with the students’ academic and professional demands. The materials currently in use often do not reflect the students’ sociocultural background, leading to low engagement and limited learning effectiveness. This study aims to address this gap by designing English reading comprehension materials infused with Besemah cultural elements. Employing the Design and Development Research (DDR) methodology, the research collected data through questionnaires and interviews with both students and faculty members. The developed materials were subjected to a comprehensive validation process involving content experts in reading and instructional design, an English language practitioner, and feedback from 15 Social Welfare students focusing on clarity, engagement, and practical use. Results revealed that integrating Besemah cultural content substantially improved students’ motivation and understanding, making learning more meaningful and contextually appropriate. The study concludes that culturally responsive instructional materials not only enhance language acquisition but also foster a sense of cultural identity and appreciation, offering a valuable model for localized educational innovation across various disciplines.